Photochemically mediated synthesis of a gold colloid by dithizone and its application in the amperometric sensing of thiocyanate - Gupta S.; Prakash R. (My University, 2025)
This paper highlights a one-step facile approach for the photochemically assisted synthesis of stable gold colloids (Au) using dithizone (DTZ) without any extra controls, viz. surfactant, seeds, pH etc. Although dithizone chemistry has been documented extensively in scientific reports, it is amazing to note that there are scarcely any reports published so far on the photochemically mediated formation of gold nanostructures using dithizone. The as-prepared electroactive hybrid nanomaterial was extensively investigated using various characterization techniques, including UV-visible spectroscopy, FT-IR, cyclic voltammetry, amperometry, TEM, FESEM and XPS. The formation of the gold nanostructure over time by exposure to light using dithizone was ascertained, with the results complemented by time dependent UV-visible as well as TEM studies. A conceivable reaction mechanism for the formation of the gold nanostructure has also been proposed. The use of dithizone as a reductant as well as a stabilizer offers great advantages in terms of simplicity during synthesis, i.e., a one-pot synthesis, use of aqueous/organic media, no external reducing agent and a very limited post-synthesis work-up. Furthermore, an electroactive advanced hybrid nanomaterial derived from nanoscale gold protected with dithizone (DTZ) and its oxidation product (DTZH) has been utilized for the amperometric sensing of hazardous thiocyanate. The modified electrode with the hybrid material efficiently electrocatalyzes the oxidation of thiocyanate at a potential of 0.55 V vs. AgCl/Ag and shows a linear response toward thiocyanate sensing with a sensitivity of 0.016 μA nM-1 and a limit of detection of 23.348 nM at a S/N (signal-to-noise ratio) of 3. The electrochemistry behind the sensing of thiocyanate is possibly due to electrostatic interactions (DTZH⋯SCNn-⋯Aum+⋯SCNn-⋯DTZH complexation) and the conducting gold nanoparticles facilitating the efficient collection and transfer of electrons to the modified electrode. © The Royal Society of Chemistry 2015.